PENGARUH MINUMAN BAWANG PUTIH TERHADAP PENURUNAN TEKANAN DARAH PASIEN HIPERTENSI DI PUSKESMAS TELAGA DEWA KOTA BENGKULU TAHUN 2022 - Ruadya Tuzzarah Dewi; Des Metasari; Murwati Murwati (Universitas Pahlawan Tuanku Tambusai, 2022)
Hypertension is still a major problem in the world. In almost every country, especially developed countries, hypertension is a public problem which is often the cause of death. The aim of the research was to determine the effect of garlic drink on reducing blood pressure in hypertensive patients in the Telaga Dewa Health Center Work Area, Bengkulu City in 2022. The method in this study was quantitative, using quasy experimental research with a pre post test one group design approach. The sample in the study was 15 respondents who were selected according to the inclusion and exclusion criteria. This study used the Wilcoxon Test statistic. The results of this study showed that the mean systolic value before the intervention was 150 mmHg and the mean systolic value after the intervention was 121.33 mmHg. The mean diastolic value before the intervention was 91.33 mmHg and the mean diastolic value during the intervention was 80.33 mmHg. The statistical test results of the Wilcoxon Test obtained a value of ρ value = 0.000 < α = 0.05, H0 was rejected and Ha was accepted, meaning that there is an effect of garlic drink on systolic blood pressure at the Telaga Dewa Health Center, Bengkulu City in 2022. The conclusion in this study is that garlic can reduce blood pressure in hypertensive patients. The suggestion in this study is that hypertensive patients can use garlic in preventing recurrence of hypertension. Keywords: Garlic, Hypertension